Physicochemical and biological properties of a new bioceramic root canal filling material for primary teeth - Ochoa Rodríguez, Victor Manuel [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
An ideal root canal filling for primary teeth should not hinder the eruption of permanent successor teeth, but rather, should be resorbed as the primary teeth roots are physiologically resorbed. Bio-C Pulpecto - Bio CP (Angelus, Londrina, Brazil) was recently developed as the first bioceramic filling material for primary teeth. The objectives of publication 1 were to evaluate radiopacity, setting time, pH, cytocompatibility and the potential for mineralization of Bio-CP compared to Calen thickened with zinc oxide (Calen-ZO) and zinc oxide eugenol (ZOE). The physicochemical properties were evaluated according to ISO 6876. Saos-2 (human osteoblast-like lineage) exposed to material extracts were subjected to methylthiazolyl tetrazolium, neutral red, alkaline phosphatase (ALP) activity and production of mineralized nodule. The results were analyzed using one-way or two-way ANOVA and Tukey or Bonferroni post-tests (α=0.05). All materials showed radiopacity greater than 3 mm Al. Bio-CP had a lower pH than Calen-ZO, but higher than ZOE. Calen-ZO and Bio-CP did not set. The ZOE setting time was 110 min. The order of cytocompatibility was Calen-ZO > Bio-CP > ZOE (1:2, 1:4 dilutions) and Calen-ZO > Bio-CP = ZOE (1:12, 1:24 dilutions) and Calen-ZO = Bio - CP>ZOE (dilution 1:32). Bio-CP induced greater ALP activity at 7 days, and greater production of Cal-mineralized proteins, compared to greater numbers of people (p<0.05). The objectives of publication 2 were evaluated for solubility (mass loss), using modified methodology from ISO 6876; filling capacity, volumetric change and presence of voids, by means of micro computed tomography (micro-CT), of Bio-CP in comparison with Calen-ZO and ZOE. In addition, the distribution of elements on the surface of the materials and the crystalline phases of Calen-ZO and Bio-CP were evaluated by energy scattering X-ray scanning electron microscopy (SEM-EDX) and X-ray diffraction (XRD). The materials were placed in polyethylene tubes of 1 or 2 mm in diameter and immersed in water or PBS (Phosphate-Buffered Saline) for 30 days. Data were analyzed by two-way ANOVA and Tukey or Kruskal-Wallis and Dunn (α=0.05). Solubility was greater than 7% for all materials; the order was ZOE>Calen-ZO=Bio-CP. Calen-ZO and Bio-CP were more soluble in water than in PBS. Most materials showed higher solubility in 2 mm tubes, both in PBS and in water. Only Calen-ZO and ZOE were analyzed on micro-CT because Bio-CP separated into two phases during scanning. There was no difference in filling capacity between the materials. Calen-ZO had greater volumetric loss and presence of voids than ZOE in water, but there was no difference in PBS. Precipitates on the surface of BioCP and Calen-ZO, corresponding to hydroxyapatite, were drawn after printing in PBS. It was concluded that BioCP presented adequate physicochemical properties, citocompatibility and potential to induce mineralization. All materials showed adequate filling capacity. Bio-CP and Calen-ZO showed lower solubility than ZOE, regardless of immersion medium and tube diameter, except for the 2 mm tube immersed in PBS, and produced hydroxyapatite when immersed in PBS. Micro-CT was not suitable for Bio-CP evaluation. Although Bio-CP has the potential to become a suitable material for filling primary teeth, its composition needs to be revised to achieve chemical stability.

Bio-C Pulpecto - Bio CP (Angelus, Londrina, Brasil) foi recentemente desenvolvido como o primeiro material obturador biocerâmico para dentes decíduos. Os objetivos da publicação 1 foram avaliar radiopacidade, tempo de presa, pH, citocompatibilidade e o potencial para induzir mineralização do Bio-CP em comparação com Calen espessado com óxido de zinco (Calen- ZO) e óxido de zinco e eugenol (ZOE). As propriedades físico-químicas foram avaliadas de acordo com ISO 6876. Saos-2 (linhagem de osteoblastos-like de humanos) expostos a extratos dos materiais foram submetidos a ensaios de metiltiazolil tetrazólio, vermelho neutro, atividade de fosfatase alcalina (ALP) e produção de nódulos mineralizados. Os resultados foram analisados empregando ANOVA one-way ou two-way e pós-testes de Tukey ou Bonferroni (α=0,05). Todos os materiais apresentaram radiopacidade superior a 3 mm Al. Bio-CP teve pH mais baixo que Calen-ZO, porém mais elevado que ZOE. Calen-ZO e Bio-CP não tomaram presa. O tempo de presa de ZOE foi de 110 min. A ordem de citocompatibilidade foi Calen-ZO> Bio-CP> ZOE (diluições 1: 2, 1: 4) e Calen-ZO> Bio-CP = ZOE (diluições 1:12, 1:24) e Calen-ZO = Bio- CP> ZOE (diluição 1:32). Bio-CP induziu maior atividade ALP em 7 dias, e maior produção de nódulos mineralizados, em comparação com Calen-ZO (p < 0,05). Os objetivos da publicação 2 foram avaliar a solubilidade (perda de massa), empregando metodologia modificada da ISO 6876; e capacidade de preenchimento, alteração volumétrica e presença de vazios, por meio de microtomografia computadorizada (micro-CT), do Bio-CP em comparação Calen- ZO e ZOE. Além disso, foram avaliadas a distribuição de elementos na superfície dos materiais e as fases cristalinas de Calen-ZO e Bio-CP por microscopia eletrônica de varredura com raio-X por dispersão de energia (SEM-EDX) e difração de raios-X (XRD). Os materiais foram inseridos em tubos de polietileno de 1 ou 2 mm de diâmetro e imersos em água ou PBS (solução salina tamponada com fosfato) por 30 dias. Os dados foram analisados por ANOVA two-way e Tukey ou Kruskal-Wallis e Dunn (α=0,05). A solubilidade foi superior a 7% para todos os materiais; a ordem foi ZOE>Calen-ZO=Bio-CP. Calen-ZO e Bio-CP foram mais solúveis em água que em PBS. A maioria dos materiais apresentou maior solubilidade em tubos de 2 mm, tanto em PBS quanto em água. Apenas Calen-ZO e ZOE foram analisados em micro-CT porque Bio-CP se separou em duas fases durante o escaneamento. Não houve diferença na capacidade de preenchimento entre os materiais. Calen-ZO teve maior perda volumétrica e presença de vazios do que ZOE em água, mas não houve diferença em PBS. Precipitados na superfície de Bio-CP e Calen-ZO, correspondentes à hidroxiapatita, foram detectados após imersão em PBS. Concluiu-se que Bio-CP apresentou propriedades físico-químicas adequadas, citocompatibilidade e potencial para induzir mineralização. Todos os materiais apresentaram boa capacidade de preenchimento. Bio-CP e Calen-ZO apresentaram solubilidade menor que ZOE, independentemente do meio de imersão e diâmetro do tubo, com exceção do tubo de 2 mm imerso em PBS, e produziram hidroxiapatita quando imersos em PBS. Micro-CT não foi adequada para avaliação do Bio-CP. Embora Bio-CP tenha potencial para se tornar um material adequado para obturação de dentes decíduos, sua composição precisa ser revista para se obter estabilidade química.
Propriedades físico-químicas e biológicas de um novo material obturador biocerâmico de canal radicular para dentes decíduos
Keywords: Tooth, Deciduous; Endodontics; X-Ray microtomography; Chemical phenomena; Dente decíduo; Endodontia; Microtomografia por Raio-X; Fenômenos químicos